A cohort study of mortality and cancer incidence in ethylene oxide production workers. - Hogstedt, C (1979)
Ethylene oxide, important as an intermediate product in the chemical industry and for sterilising hospital equipment, is mutagenic in several organisms; carcinogenicity has been suspected although this had not been supported by clinical data. Ethylene oxide has been produced by a Swedish company since the beginning of the 1940s. This paper describes a cohort study of the mortality and the cancer incidence among full-time exposed workers in ethylene oxide production, a group of maintenance workers with intermittent exposure and a group of unexposed controls. Investigation of the production processes in the building at different times has shown that workers were exposed to ethylene dichloride, ethylene chlorohydrin, ethylene, and small amounts of bis-(2-chloroethyl) ether as well as to ethylene oxide and traces of other chemicals. The full-time exposed cohort shows a considerable excess mortality deriving mainly from increased mortality from tumours and also from diseases of the circulatory system. The cancer incidence study, including living persons with malignancies, showed a significant excess in the full-time cohort. Of the 16 patients with tumours in the two more exposed cohorts there were three cases of leukaemia, six of tumours in the alimentary tract and four of urogenital malignancy. The excess mortality and cancer incidence cannot be attributed to any particular chemical in the production process, but ethylene oxide and ethylene dichloride are the prime suspects.